Leg restrainer. - Ab. Ghani, Rijalani (2010)
The present invention discloses, a livestock leg restraining apparatus that seeks to provide a means to restrain the hind legs of livestock animals thus enabling operations personnel to approach said animals from behind in order to carry out animal husbandary procedures. The livestock leg restraining apparatus of the present invention comprises of a first and second support members, wherein each of the support members consists of an upper and lower locking means extending between a front leg and a rear leg in a resting position, the fixed end portions of the blocks are pivoted at regularly spaced intervals along the length of a first beam and a second beam, the first and second support members further including a third beam below the lower locking means and extending between the front and rear legs; and a pair of rods capable of being extended through the spacing intervals of the upper and lower locking means and movable towards the front leg and the rear leg by way of forcing the free ends of the blocks to rotate from its resting position until the rods make contact with the legs of the animal to restrain the legs.